1997
DOI: 10.1007/bf01412003
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular changes associated with postischaemic hypoperfusion in rats

Abstract: The present study was undertaken to explore the cause of postischaemic hypoperfusion through morphological observations of the microstructure of brain cortex capillaries in rats with postischaemic hypoperfusion. Sixteen rats were used. The left middle cerebral artery of each animal was occluded for one hour (n = 8) or 2 hours (n = 8) and was followed by reperfusion for 2 hours. The regional cerebral blood flow (rCBF) of the ischaemia induced brain cortex was monitored continuously during the experiment and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…14 Vasogenic edema appears later than cytotoxic edema in severe ischemic injury. 15,16 It leads to a rise in net water content of the ischemic brain tissue. However, vasogenic edema formation is not restricted to the infarcted tissue but spreads into the extracellular space of the peri-infarct tissue.…”
Section: Discussionmentioning
confidence: 99%
“…14 Vasogenic edema appears later than cytotoxic edema in severe ischemic injury. 15,16 It leads to a rise in net water content of the ischemic brain tissue. However, vasogenic edema formation is not restricted to the infarcted tissue but spreads into the extracellular space of the peri-infarct tissue.…”
Section: Discussionmentioning
confidence: 99%
“…First, it might be due to microvascular impairment and incomplete microcirculatory reperfusion (IMR) or no re-flow (a failure to achieve adequate reperfusion of cerebral microcirculation) that are observed in ischemic regions [49]. Second, it might be the result of endothelial swelling [50] and compression by swollen astrocyte end-feet [51] and/or transient constriction of smooth muscle cells [52]. Alternatively, Tsuchidate, et al undertook a detailed study, using a rat model of ischemia and autoradioactive imaging techniques confirmed that after reperfusion some areas of ischemic tissues experienced hyperperfusion [53].…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] Consequently, damage of neuronal tissue results in increased blood-brain barrier permeability. Direct ischemic damage of brain vessels 16 may add to the problem, and reperfusion, eg, after thrombolysis, may also exacerbate blood-brain barrier damage. 26 The greater the brain tissue and vessel damage, the greater is the water increase in extracellular space of infarction, and because of bulk flow, secondarily of peri-infarct tissue.…”
Section: Discussionmentioning
confidence: 99%